Why has it been so difficult to prove the efficacy of alpha-1-antitrypsin replacement therapy? Insights from the study of disease pathogenesis - Dickens JA; Lomas DA (Dove Medical Press, 2011)
Jennifer A Dickens, David A LomasDepartment of Medicine, University of Cambridge, Cambridge Institute for Medical Research, Wellcome Trust/MRC Building, Cambridge, UKAbstract: Alpha-1-antitrypsin is the most abundant circulating protease inhibitor. It is mainly produced by the liver and secreted into the circulation where it acts to prevent excessive proteolytic damage in the lungs by the enzyme neutrophil elastase. The most common severe deficiency allele is the Z mutation, which causes the protein to self-associate into ordered polymers. These polymers accumulate within hepatocytes to cause liver damage. The resulting lack of circulating α1-antitrypsin predisposes the Z homozygote to proteolytic lung damage and emphysema. Other pathways may also contribute to the development of lung disease. In particular, polymers of Z α1-antitrypsin can form within the lung where they act as a pro-inflammatory stimulus that may exacerbate protease-mediated lung damage. Researchers recognized in the 1980s that plasma α1-antitrypsin levels could be restored by intravenous infusions of purified human protein. Alpha-1-antitrypsin replacement therapy was introduced in 1987 but subsequent clinical trials have produced conflicting results, and to date there remains no widely accepted clinical evidence of the efficacy of α1-antitrypsin replacement therapy. This review addresses our current understanding of disease pathogenesis in α1-antitrypsin deficiency and questions why this treatment in isolation may not be effective. In particular it discusses the possible role of α1-antitrypsin polymers in exacerbating intrapulmonary inflammation and attenuating the efficacy of α1-antitrypsin replacement therapy.Keywords: α1-antitrypsin deficiency, emphysema, augmentation therapy